MODEL PENDUGAAN LIMBAH DALAM PENGUPASAN VENIR KAYU MERANTI DAN RAMIN - Suwidji Basuki; Rachman Effendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The wood waste in plywood manufacturing can be used as fuel in the boiler so it is worth while to know how much waste is produced. The data obtained can be used as input to determine the amount of fuel to be purchased from outside source.In plywood making most waste is produced at peeling process, i.e. at rotary cutter, it could make up to 80 % of the total waste produced.This study showed that the waste of individual log is significantly affected by log diameter and log quality, the relationship is given by regression model.